Efek Pemberian Sari Buah Belimbing Manis (Averrhoa carambola Linn.)terhadap Kerusakan Histologis Hepar Tikus Putih(Rattus norvegicus) yang Diinduksi Parasetamol - Cahyaningrum, Handayani Putri; Listyaningsih, Endang; Handayani, Selfi (Nexus Biomedika, 2013)
Background: Star fruit (Averrhoa carambola Linn.) juice contains flavonoids, epicatechins, proanthocyanidins, and tanins that can protect liver from free radicals. The objectives of this research were to know the effect of star fruit (Averrhoa carambola Linn.) juice to liver histological damage of albino rat induced by paracetamol. Methods: This was laboratory experimental research with post test only controlled group design. Samples were 28 male rats from Wistar type, 2-3 months old and + 200 g of each weight. Samples were divided into 4 groups of 7 rats each. Sampling technique used in this research was incidental sampling. The control group (K) and the first treatment group (P1), rats were administered aquadest for 14 days. The second treatment group (P2), rats were administered star fruits juice with the concentration of 50% 2ml/200 g body weight of rat and the third group (P3), rats were administered star fruits juice with the concentration of 100% 2ml/200 g body weight of rat for 14 days. Paracetamol was administered to groups of P1, P2, and P3 on the 12th, 13th, and 14th day. On the 15th day, rats were sacrificed and their livers were made for preparation with paraffin block method which were stained HE. Liver histological features were assessed based on quantifying of pyknosis, karyorhexis, and karyolysis. Data were analyzed using the One-Way ANOVA test (Î± = 0.05) and continued with Post Hoc Multiple Comparisons (LSD) test (Î± = 0.05). Results: Statistically, the One-Way ANOVA test showed that there were significant differences of liver damage score between K â P1, K â P2, K â P3, P1 â P2, P1 â P3, and P2 â P3. Conclusion: Star fruit juice decreased the liver histological damage of albino rat (Rattus norvegicus) induced by paracetamol. Key words: star fruit juice, paracetamol, liver histological damage, albino ratÂ